Assessing the Relationship between Demographic Attributes and Patients’ Views of Hospital Environment - Khadka, Shrijana; Nyaupane, Netra Prasad; Timalsena, Chiranjibi (Baneshwor Campus Journal of Academia, 2024)
The objective of this study was to examine the relationship between patient demographic factors (gender, age, marital status) and their perception of a patient-friendly hospital environment. A cross-sectional study was conducted using a questionnaire to collect data from 41 patients at a hospital in Kathmandu, Nepal. The questionnaire assessed perceptions of privacy, visitation, amenities, way finding, and other aspects that contribute to a patient-friendly environment. Correlation analysis was used to analyze the relationship between demographic variables and overall satisfaction. Most respondents were younger, female patients. Descriptive analysis found neutral to average satisfaction across different environment domains. Correlation analysis showed no significant relationships between gender, age, marital status and perception of a patient-friendly environment (p>0.05 for all). Patient demographics did not appear to influence perceptions of a patient-friendly environment in this study. While most domains scored neutrally, opportunities remain to enhance certain areas like bathroom accessibility and parking. Larger studies are needed to further understand how hospitals can optimize their physical environments to better support patients.